Konsep Ideal Presidential Threshold Dalam Pemilihan Umum Presiden dan Wakil Presiden Dalam Perubahan Undang-Undang Pemilu Pasca Putusan Mahkamah Konstitusi Nomor: 62/PUU/XXII/2024 - T, Thorik; D, Suhariyanto; I, Ismail (Media Hukum Indonesia (MHI), 2025)
Indonesia is a country that practices electoral democracy, a system of government that allows all citizens to choose one of several candidates competing in elections. Previously, the Presidential Threshold threshold of 20% was considered to be unjust and disproportionate, especially for small parties. This study examines the ideal Presidential Threshold that can provide access to justice for all parties, especially small and medium-sized parties. This study utilizes Hans Kelsen's Theory of Legislation and Sudikno Mertokusumo's Theory of Legal Certainty. This study discusses the need for a rational and proportional PT percentage that is neither 0% nor as high as 20%, to ensure representation, healthy competition, and political stability. The purpose of this study is to analyze the implications of Constitutional Court Decision Number 62/PUU-XXII/2024 on the Presidential Threshold regulation and analyze the ideal concept of the Presidential Threshold. The research method is normative juridical. The results of the study show that the ideal concept of the presidential threshold in Indonesia is a significant reduction in the threshold for presidential and vice presidential nominations by 4%, which is paralleled by the parliamentary threshold with a mechanism where parties that have not reached the threshold for DPR seats or valid election votes of 4% can nominate with the support of factions and political parties for presidential and vice presidential nominations in the election. This is to provide a more open space for competition and guarantee the constitutional rights of all political parties participating in the election in accordance with Article 6A paragraph (2) of the 1945 Constitution of the Republic of Indonesia.